Elementary School Teachers’ Perspectives on Integrating Technology, Information, and Communication in Education - Ratna Hidayah; Muna Fauziah (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of information and communication technology (ICT) in education offers significant opportunities for enhancing teaching and learning in the 21st century. This study aims to analyze elementary school teachers’ perceptions of ICT utilization in public schools in Kebumen Regency. A quantitative, cross-sectional survey design was employed. Data were collected from 109 elementary school teachers through online questionnaires distributed via Google Forms. Responses were measured using a 4-point Likert scale ranging from 1 (strongly disagree) to 4 (strongly agree). Descriptive statistical analysis was used to interpret the data. Findings indicate that teachers hold highly positive perceptions of ICT integration in learning. The perceived impact of ICT on student interest and motivation received an average score of 3.79, while the perceived benefits of ICT in learning scored 3.72. Teachers also acknowledged the educational value of ICT (mean score: 3.57) and expressed confidence in their ICT competence (mean score: 3.29). All scores fall within the high to very high category, suggesting strong support for ICT usage in the classroom. These results highlight a favorable outlook among primary school teachers regarding ICT in education. However, limitations exist, as the study focuses solely on elementary-level educators. The generalizability of findings to higher educational levels may be limited. Teachers in Kebumen exhibit strong support for ICT integration in primary education. Future research should consider longitudinal studies or expand to higher education contexts to assess the broader impact of ICT on teaching and learning outcomes.